Strategic management and business development ("Journal "U". Economy. Management. Finance.", 2025)
The article examines the key aspects of strategic management and its impact on business development. The role of the analysis of the external and internal environment, the formation of strategies is analyzed. Special attention is paid to the issues of digital transformation, innovation and crisis planning. Examples of successful application of the strategic approach in companies are considered. The conclusion is made about the importance of strategic management to ensure the sustainable development of an organization in a dynamically changing environment
Keywords: strategic management; business development; environmental analysis; digital transformation; innovation; interviews